A clinical study of the skin changes in pregnancy in Kashmir valley of north India: A hospital based study - Iffat Hassan; Safia Bashir; Shahnaaz Taing (Wolters Kluwer Medknow Publications, 2015)
Background: Pregnancy is associated with multiple skin changes, most of which are physiological in nature, being the direct result of expected modifications of the hormonal, vascular, metabolic or immunologic status in pregnant females. Pregnancy however is also associated with certain pruritic eruptions, which not only cause distress to the pregnant female, but may influence the fetal outcome as well. Objective: The objective of this study was to determine the pattern of skin changes associated with pregnancy and to identify the various clinical types of pregnancy specific dermatoses (PSDs). Materials and Methods: The study was a cross sectional study carried out at the out-patient Department of Gynecology and obstetrics of our hospital. A total of 650 pregnant females, irrespective of their parity and gestational age were screened for the presence of any dermatological complaint. Results: The age of the study population ranged from 17 to 39 years (mean age: 24 years). The study population included 272 (42%) primigravidae and 378 (58%) multigravidae. Physiological skin changes of pregnancy were seen in all patients, out of which linea nigra was the most common change, seen in 520 (80%) cases. Specific dermatoses of pregnancy were seen in 32 (4.9%) cases, which included (in the decreasing order of frequency) prurigo of pregnancy (50% cases), intrahepatic cholestasis of pregnancy (25% cases), polymorphic eruption of pregnancy (22% cases) and pemphigus gestationis (3% cases). Conclusion: Skin changes were seen in 100% of pregnant females in this study, the major proportion being formed by physiological skin changes of pregnancy though PSDs were also seen in a significant number.